A life with seizures: Argentine patients' perspectives about the impact of drug-resistant epilepsy on their lives. (December 2018) - Sarudiansky, Mercedes; Korman, Guido Pablo; Scévola, Laura; Oddo, Silvia; Kochen, Silvia; D'Alessio, Luciana
Highlights: Patient's perspectives of illness are important to develop interventions in epilepsy. Qualitative studies in epilepsy patients are scarce in Latin American countries. Explanatory models of illness are important in terms of its impact on patient's life. Similarities and differences were found between Argentine and first-world patients. Abstract: Purpose: To understand the experience of drug-resistant epilepsy in patients from Argentina, a developing nation. Method: A qualitative approach using semi-structured interviews was used to gain an in-depth and contextual understanding of the perspectives of 20 patients with DRE. Data collection and analysis were followed by an inductive and interpretive approach informed by the principles of thematic analysis. Results: Six main themes emerged: 1) Characteristics of the illness, including seizure features -unpredictability, presence of auras, physical and cognitive consequences- and how patients relate with the use of antiepileptic drugs; 2) interactions with health system, regarding the features of the Argentine's health system, and patient's health-seeking behaviours; 3) beliefs about the illness, including psychosocial, biological and folk explanatory models; 4) beliefs about how other people perceive them, which included prejudice, responsibility and overprotection; 5) self-perception, and 6) impact of the illness on their activities. Conclusions: This information might be useful to help in the development of a conceptual model of the impact epilepsy on patients' lives. Many of the topics mentioned as relevant in Argentina coincide with those highlighted in studies that were carried out in first-world countries. However, additional topics were also reported including the role of traditional healing in health-seeking behaviour and explanatory models of illness. It is important to understand these perspectives to develop appropriate psychosocial interventions for this specific population.